Implementasi Prinsip Hukum Kontrak dalam Sengketa Tanah: Pendekatan Ilmiah terhadap Putusan Nomor 11/PDT/2020/PT MND - Rifaldo Aditya; Kenzie Samuel Tumondang (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
Land disputes often arise due to conflicting ownership claims and legal interpretations of land rights. This study analyzes the application of contract law principles in resolving civil land disputes through a case study of Decision Number 11/PDT/2020/PT MND issued by the Manado High Court. The findings indicate that the principles of pacta sunt servanda and good faith play a crucial role in ensuring legal certainty and fairness for all parties. The court’s ruling affirms that a valid agreement must be respected and enforced accordingly. Furthermore, this study recommends strengthening alternative dispute resolution mechanisms such as mediation and arbitration to enhance the efficiency of land dispute resolution.